PROSES AUDIT INTERNAL KAS DALAM MEMINIMALISIR KESALAHAN PENCATATAN TRANSAKSI TELLER PADA BANK BTN KANTOR CABANG JAKARTA CAWANG - Farhan Luthfi (2021)
Banking competition in Indonesia is currently getting tighter, this encourages banks to implement more optimal strategies. The competition between banks in Indonesia demands the internal conditions of the banking system as a factor that needs to be considered. One of the strategies that can be used by the Bank to ensure that tellers have performed well and support the suitability of cash balances for teller operational transactions is to conduct an internal audit of teller cash. Therefore, Bank BTN Jakarta Cawang Branch has a procedure for checking cash teller transactions. So, in this Final Project Report, we discuss the process of checking cash tellers at Bank BTN Jakarta Cawang Branch. The purpose of this final report is to know the cash teller audit procedures, risk management, obstacles and solutions. The sources of discussion of the Final Project Report used are books and interviews. The result of the Final Project Report obtained is that the cash teller audit implementation consists of four stages and the implication is to help assess the suitability of financial transactions at cash tellers against the applicable Standard Operating Procedures